Tautomerism in the Guanyl Radical - Chatgilialoglu, Chryssostomos; Caminal, Clara; Altieri, Alessio; Georgios C. Vougioukalakis; Mulazzani, Quinto G.; Gimisis, Thanasis; Guerra, Maurizio (J. Am. Chem. Soc., 2006)
Despite a few decades of intense study, a full description of tautomers of one-electron-oxidized guanine remains to be achieved. Here we show that two of these tautomers are produced by the protonation of an 8-haloguanine electron adduct. The rate constants for the reactions of hydrated electrons (e aq-) with a variety of 8-substituted guanine derivatives have been measured by a pulse radiolysis technique and correlated with both inductive and resonance components of the substituents. The fate of electron adducts was investigated by radiolytic methods coupled with product studies and addressed computationally by means of time-dependent DFT (TD-B3LYP/6- 311G**//B1B95/6-31+G**) calculations. The reaction of eaq- with 8-haloguanosine or 8-halo-2′- deoxyguanosine produces the first observable transient species that decay unimolecularly (k = 1 × 105 s-1 at 22 °C) to give the one-electron oxidized guanosine or 2′-deoxyguanosine. Theory suggests that the electron adducts of 8-bromoguanine derivatives protonated at C8 form a $π$-complex, with the Br atom situated above the molecular plane, that is prompt to eject Br. The two short-lived intermediates, which show a substantial difference in their absorption spectra, are recognized to be the two purine tautomers (i.e., iminic 7 and aminic 3 forms). The spin density distributions of the two tautomers are quite different at the O6 and N10 positions, whereas they are very similar at the N3, C5, and C8 positions. The resonance structures of the two tautomers are discussed in some detail. B1B95/6-31+G** calculations show also that the tautomerization from the iminic (7) to the aminic (3) arrangement is a water-assisted process. © 2006 American Chemical Society.